Нужно ; з раскройте скобки и получившееся выражение: а) (x+y)+(y-x) б)( a--b) в) (c-+d) г)(u+-u) д)m-(n-p-m) е)(a++-c) ж)(k+--k) з)(b+--a)

dgrigoref dgrigoref    3   24.05.2019 18:30    1

Ответы
misselYT misselYT  01.10.2020 10:56

Объяснение:

a)

(x+y)+(y-x)=x+y+y-x=2y;

б)

(a-b)-( a-b)=a-b-a+b=0;

в)

(c-d)-(c+d)= c-d-c-d=-2d;

г)

(u+v) -(v-u)=u+v-v+u=2u;

д)

m-(n-p-m)=m-n+p+m=2m-n+h;

е)

(a+b) -(b+c) -(a-c)= a+b-b-c-a+c=0;\\

ж)

(k+m)-(k-m)-( m-k)= k+m-k+m-m+k=k+m;

з)(b+1) -(a-1) -(b-a) =b+1-a+1-b+a=2.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра